Corporate Social Performance in Emerging Economies: Insights from Indonesian Scholarship - Nouke Sysca Oroh (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: The rapid growth of sustainability, ESG, and stakeholder accountability has elevated Corporate Social Performance (CSP) into a strategic priority for organizations. However, despite increasing scholarly attention, CSP research in Indonesia remains fragmented, limiting a comprehensive understanding of its intellectual development. This study aims to map the intellectual structure, thematic evolution, and emerging trends of CSP research in Indonesia. Research Method: A systematic review integrated with bibliometric analysis was conducted using the PRISMA framework. Data were collected from the Scopus database and analyzed using publication trends, citation analysis, and keyword co-occurrence mapping through VOSviewer. Results and Discussion: The findings reveal a substantial increase in CSP research, particularly after 2020, reflecting growing academic interest in sustainability-related issues. Stakeholder Theory, Agency Theory, Resource-Based View, Legitimacy Theory, and Signaling Theory emerged as the dominant theoretical foundations. Six major research themes were identified: Corporate Social Responsibility and Corporate Performance; ESG, Sustainability, and Sustainable Development; Financial Performance and Firm Value; Corporate Governance and Accountability; Sustainability Reporting and Disclosure Practices; and Sectoral and Emerging Sustainability Contexts. Implications: The results indicate a clear shift from CSR and disclosure-focused studies toward ESG integration, sustainable finance, governance, and sustainability-driven value creation. Originality: This study contributes by providing a comprehensive overview of the evolution of CSP research in Indonesia and offers directions for future research, policy development, and corporate sustainability practices.